Cross-talk of instructed and applied arbitrary visuomotor mappings - Waszak, Florian; Wenke, Dorit; Brass, Marcel (Acta psychologica, 2008)
Humans are able to perform any voluntary motor response to any environmental stimulus. This cornerstone of the flexibility of human behaviour has been investigated under the label of arbitrary visuomotor mapping. The focus of research has been the question as to how these mappings are executed once the subjects have been instructed appropriately. However, one question has been rather neglected thus far: what, in the first place, enables humans to instantaneously implement any arbitrary S–R mapping by mere instruction! We report an experiment assessing the cross-talk of arbitrary S–R mappings as a part of the instructed task representation, on the one hand, and the cross-talk of repetitively applied mappings, on the other hand. The results show a behavioural dissociation of the cross-talk elicited by instructed and applied mappings, suggesting that the first occurs on the level of task-set, whereas the latter occurs on the level of specific S–R associations.